Analisis Biaya Kuliah Saat Pandemi Covid-19 Pada Mahasiswa Program Studi Pendidikan Ekonomi FKIP UPR - Junaris Situmorang; Rinto Alexandro; Sundari Sundari; Hendrowanto Nibel (FKIP, Universitas Palangka Raya, 2022)
Tuition fees in education contain the understanding as costs that must be incurred by students in following the educational process from the beginning to the final stage of education. Objective from study this For Know Analysis Cost Studying Moment Covid19 Pandemic on Study Program Students Education Economics FKIP University Palangka Raya. Method used in study this is method qualitative with method analysis descriptive that is the researcher is intended to collect data or information about an existing phenomenon. The types of data used are primary data and secondary data. Data collection techniques consisting of observation, interviews and documentation. Data analysis was used using techniques from three stages of activities carried out sequentially, namely data reduction, data presentation, and data analysis withdrawal conclusion. From result study found that quantity cost issued lectures by each college student varies, there are addition cost studying that is on cost internet quota, which was originally IDR 100,000, was issued when pandemic cost internet quota is experiencing enhancement that is IDR 250,000 is caused by online learning so students must have internet quota to access the internet, zoom meetings, google meet, whatshaap, YouTube and other learning media, meanwhile the UKT costs have decreased. IDR 1,000,000, and for the cost of boarding/daily costs, it adjusts from parental submissions. Then for monthly needs, it increased from Rp. 1,000,000 to Rp. 2,000,000, while for cost Duty tuition fees activity student, and cost health is must cost prepared student who is at basic college student no can miss from cost the in Century pandemic this for example the cost of KKN and PPL that must be issued IDR 300,000, next cost related health with protocol health for purchase for example vitamins, masks and hand sanitizer reach IDR 50,000. Whereas for cost Duty covers print out or related with ATK you can reach IDR 50,000.